Osimertinib Resistance With a Novel EGFR L858R/A859S/Y891D Triple Mutation in a Patient With Non-Small Cell Lung Cancer: A Case Report - Yang, Yanli; Zhang, Xing; Wang, Ruixiao; Qin, Jiayue; Wang, Juan; Li, Zhimin; Song, Xia (Frontiers in Oncology, 2020)
Targeted drug therapy based on the types of epidermal growth factor receptor (EGFR) gene mutations has been widely used in the diagnosis and treatment of patients with non-small cell lung cancer (NSCLC). With the development of next-generation sequencing (NGS) technology, more and more EGFR-tyrosine kinase inhibitor (TKI) resistance mutation sites have been revealed. Here, we report a novel EGFR L858R/A859S/Y891D triple mutation in plasma-derived circulating tumor DNA (ctDNA) was identified in a 53-year-old male patient with NSCLC resistant to osimertinib treatment, using an ultra-deep (20000X) 160-gene panel through the NGS platform. Our case confirms that dynamic monitoring of liquid biopsy based on ctDNA is conducive to the selection of targeted therapy and the realization of the patient's full course management.